HYPNOTHERAPY FOR COMPLEX PTSD IN VETERANS - Ihnatovych, Olena (Sworld-Us Conference proceedings, 2025)
This article explores the theoretical foundations, clinical applications, and empirical evidence of hypnotherapeutic interventions in addressing complex post-traumatic stress disorder (CPTSD) among military veterans and their families. The study presents